Short Communication: Nematodes associated with Robusta coffee plantations in Malang District, East Java, Indonesia - HAGUS TARNO; EYIK WIDYANSYAFICHA MARSUDI; TITI WIDJAYANTI; Yogo Setiawan (Society for Indonesian Biodiversity, 2021)
Abstract. Tarno H, Marsudi EW, Widjayanti T, Setiawan Y. 2021. Short Communication: Nematodes associated with Robusta coffee plantations in Malang District, East Java, Indonesia. Biodiversitas 22: 3306-3312. Coffee (Coffea spp.) is an important commodity in Indonesia. Nematodes have different roles, such as plant parasites and non-parasites, and are commonly found in the soil of coffee plantations. This research determined the ecological role, diversity, and abundance of nematodes in three coffee plantations in Malang District, East Java. We used a Whitehead tray to extract and isolate nematodes from the soil and root samples. Nematodes were identified based on their morphological characteristics. Analysis of variance and diversity indices were used to identify the differences among three coffee plantations. We identified eight nematode genera in the Ngantang sub-district site. In the Jatikerto Agrotechnopark and University of Brawijaya Forest sites, six genera were identified. Criconemoides, Pratylenchus, Xiphinema, Helicotylenchus are plant-parasitic nematodes, and Mononchus, Dorylaimus, Rhabditis, and Aphanolaimus are non-plant parasitic nematodes. Non-plant parasitic nematodes were more abundant than plant-parasitic nematodes in all sites. Non-plant parasitic nematode, Dorylaimus was the dominant genus in this study (272 individuals), ca. 35% of the total nematodes collected. In this study, the differences between coffee plantations and soil pH influence nematode abundance. The nematode abundance increases when the soil pH is lower.